Academic Integrity in Indonesia: Undergraduate Students’ Views on Plagiarism - Wardani, Umi Sismia; Maharsi, Ista (English Language in Focus (ELIF), 2024)
This study aimed to identify Indonesian undergraduate students' perceptions of plagiarism in an English language education department at a private university in Indonesia. One hundred three students who were taking Academic Reading and Writing classes took part in this study. The data were collected using a 22-item questionnaire on plagiarism awareness adapted from Jereb et al. (2018). The data were analyzed descriptively to identify the participants' perceptions of plagiarism. The findings show that most students are aware of plagiarism even if it is wrong. The action was taken because of several demands from teachers or institutions, another factor was a lack of knowledge of plagiarism. It can be seen the results of the data from four aspects. The highest score belongs to the awareness of plagiarism (M= 4.2; SD= 1.138). The second-highest score belongs to the aspects of plagiarism knowledge (M= 3.12; SD= 1.118). The third-highest score is the attitude towards plagiarism (M= 2.45; SD= 1.012). The fourth-highest score belongs to the aspects of acceptability of plagiarism (M= 2.38; SD= 1.032). Then, the lowest mean score is the unknowingness of plagiarism (M= 2.18; SD= 1.092).